Facile Synthesis of Porous ZnO Nanoparticles Efficient for Photocatalytic Degradation of Biomass-Derived Bisphenol A Under Simulated Sunlight Irradiation - Wang, Yujie; Hu, Kang; Yang, Zhiyu; Ye, Chenlu; Li, Xin; Yan, Kai (Frontiers in Bioengineering and Biotechnology, 2021)
Bisphenol A (BPA) produced from biomass is a typical endocrine disrupting compound which is carcinogenic and genotoxic, and can be accumulated in water due to its extensive use and difficult degradation. In this study, the porous ZnO photocatalyst with core-shell structure and large surface area was successfully developed for the efficient photocatalytic degradation of BPA. 99% degradation of BPA was achieved in 1 h using the porous ZnO calcined at 550oC under the conditions of 30 mg/L BPA, 1 g/L ZnO and pH of 6.5. The various effect of calcination temperatures, BPA concentrations, ZnO dosages, pH and inorganic ions on the degradation performance were systemically studied. Besides, the inhibition effects of anions for the photocatalytic removal of BPA decreased in the order of H2PO4-> HCO3- > SO42- > Cl-, while the cations K+, Ca2+ and Na+ had little effect on the photocatalytic degradation of BPA. The results of scavenging experiments showed that h+, ·O2- and e- played the key role in the photocatalytic degradation process. Finally, the main pathways of BPA degradation were proposed. This work may provide a good guideline to degrade various endocrine disrupting compounds in wastewater treatment.